2021
DOI: 10.1002/bab.2270
|View full text |Cite
|
Sign up to set email alerts
|

Human neutrophil peptide 1 promotes immune sterilization in vivo by reducing the virulence of multidrug‐resistant Klebsiella pneumoniae and increasing the ability of macrophages

Abstract: By studying the expression in patients and cell modeling in vitro, antimicrobial peptides for Klebsiella were screened. Killing curve and membrane permeability experiments are used to study the antibacterial effect of antimicrobial peptides in vitro. Cytotoxicity-related indicators including lipopolysaccharide (LPS), capsule polysaccharide (CPS), and outer membrane protein expression were measured. Intranasal inoculation of pneumoconiosis was used to construct a mouse infection model, and the survival rate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…This aspect needs to be confirmed in prospective trials in order to evaluate whether HNP adds information within the multifactorial risk profile for BPD. The role of HNPs in the immune defense is currently under discussion (2,28), so our data may add new information to this topic.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This aspect needs to be confirmed in prospective trials in order to evaluate whether HNP adds information within the multifactorial risk profile for BPD. The role of HNPs in the immune defense is currently under discussion (2,28), so our data may add new information to this topic.…”
Section: Discussionmentioning
confidence: 85%
“…Antimicrobial polypeptides (APPs), a large group of proteins with pleiotropic functions, are part of the innate immune system and have direct antimicrobial capacity ( 2 , 3 ). APPs may also modulate immune defense pathways ( 4 ) and inflammatory processes ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of NP-1 have mainly focused on inflammatory-immune disease research. And NP-1 has been shown to promote immune sterilization in vivo by increasing the ability of macrophages [ 31 ] . The results published by Rivas-Santiago and Soldati, et al, who demonstrated that NP-1 was lowered in elderly people [32] and smokers [33] , are consistent with our observation that NP-1 was decreased in cardiac remodeling and hypertrophic cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in LPS-primed macrophages, HNP-1 can promote pyroptosis and increase IL-1β release through inflammasome activation via the P2X7 receptor [ 78 ]. HNP-1 was reported to increase oxidative stress and autophagy-related genes, and with this enhanced endocytosis more antigens could be processed and presented [ 79 ]. Through the P2Y6 receptor signaling pathway, HNP-1 suppresses neutrophil apoptosis, prolonging their lifespan [ 80 ].…”
Section: Immune-related Functions Relevant In the Tumor Microenvironmentmentioning
confidence: 99%